Impact of Food Ingredients (Aspartame, Stevia, Prebiotic Oligofructose) on Fertility and Reproductive Outcomes in Obese Rats. Issue 11 (25th October 2018) - Cho, Nicole A.; Klancic, Teja; Nettleton, Jodi E.; Paul, Heather A.; Reimer, Raylene A.
Abstract : Objective: This study aimed to investigate the interaction between obesity, low‐calorie sweeteners, and prebiotic oligofructose on reproductive parameters in rats. Methods: Data were derived from two separate studies of female Sprague‐Dawley rats with (1) Lean ( n = 24), (2) Obese ( n = 27), (3) Obese+Aspartame ( n = 14), (4) Obese+Stevia ( n = 15), and (5) Obese+Prebiotic ( n = 15) groups. Obesity was induced with a high‐fat/high‐sucrose diet prior to pregnancy. In one study, human‐approved doses of aspartame (5‐7 mg/kg/d) and stevia (2‐3 mg/kg/d) in drinking water were examined, and in the second, 10% prebiotics (oligofructose) in the diet was examined. Reproductive parameters, including fertility, pregnancy, and delivery indexes, were analyzed. Results: Obesity significantly reduced pregnancy index in Obese dams (60.7% successful pregnancies) compared with lean (100%). Obesity also reduced the number of pups born alive and pup survival percentage compared with those of Lean dams ( P < 0.001). Only 53.3% of rats were able to conceive in the Obese+Stevia group, but if rats did become pregnant, they had 100% pregnancy and delivery index. While prebiotic administration rescued the pregnancy index, it could not remediate pup survival percentage ( P = 0.025) in Obese dams. Conclusions: Both obesity status and dietary ingredients affect the ability to conceive. Future rigorously controlled studies designed to examine reproductive outcomes in depth are needed to confirm these findings.